An Analysis Approach for Condition Monitoring and Fault Diagnosis in Pantograph-Catenary System - Karakose, Ebru; Gencoglu, Muhsin Tunay (Ieee, 2013)
High-speed trains have a great importance for long distances. The electrical energy for trains must be continuous and uninterrupted. So, the interaction and the mechanical contact between the pantograph and the catenary must be complete. Periodic condition monitoring, fault detection and pre-estimation are extremely important in the electrical railway systems. Therefore, in this study; a condition monitoring and fault diagnosis approach for pantograph-catenary system is proposed with improved model, control and analysis methods. There are two main aims of the study. The first is a regular monitoring of the system to determine whether any failure is occur. The second is to reveal the status of fault occurrence in the future. For this purpose, the contact point analysis between the pantograph strip and the catenary is performed. The most wearied points of the pantograph strip are defined by the method of condition monitoring.
IEEE International Conference on Systems, Man, and Cybernetics (SMC) -- OCT 13-16, 2013 -- Manchester, ENGLAND
Keywords: pantograpjh; catenary; wear; condition monitoring; fault diagnosis